Innovative Strategies for Enhancing Construction Project Performance - Mohd Yamani Yahya; Waziri Abdullahi Abba; Azlina Md Yassin; Roshartini Omar; Norliana Sarpin; Rolyselra Orbintang (Journal of Technology Management and Business, 2024)
Enhancing the performance of construction projects is crucial since Nigeria’s construction industry has seen a drop in project quality, which is frequently attributed to poor planning, poor execution, and the involvement of unskilled workers. Numerous problems have resulted from this trend, including project delays, financial overruns, inferior results, and even project cancellation. In order to address this issue, this study set out to find and suggest methods for improving the performance of construction projects in Nigeria. A structured quantitative technique was used to accomplish this goal, and 150 participants from the Nigerian construction industry, including architects, quantity surveyors, civil engineers, and project managers, were given questionnaires to complete. The study produced 110 valid replies, which were then examined using the SPSS version 23.0 statistical package for social science. The survey’s findings identified seven essential strategies that enhance Nigeria’s building project performance. These strategies include efficient contract oversight, high workmanship standards, strict specification compliance, robust monitoring and control, comprehensive safety training, methodical planning and scheduling, timely project completion. The study also suggests project stakeholders to step up their efforts to assure schedule adherence, reduce fluctuation claims, and put in place efficient monitoring and feedback processes to ensure compliance with project specifications. These suggestions are meant to boost overall project performance and revitalise the Nigerian construction sector.